Autonomic nervous system modulation during an archery competition in novice and experienced adolescent archers - Carrillo, A. E.; Christodoulou, V. X.; Koutedakis, Y.; Flouris, A. D. (Journal of Sports Sciences, 2011)
We assessed autonomic nervous system modulation through changes in heart rate variability during an archery competition as well as archery performance by comparing novice and experienced adolescent archers. Seven novice (age 14.0 ± 8.5 years, body mass index 22.9 ± 4.3 kg · m-2, training experience 0.4 ± 0.3 years) and ten experienced archers (age 16.5 ± 10.3 years, body mass index 22.4 ± 3.1 kg · m-2, training experience 4.1 ± 0.9 years) volunteered. Using beat-by-beat heart rate monitoring, heart rate variability was measured for 20 s before each arrow shot during two rounds of competition. We found that, compared with novices, experienced adolescent archers: (i) take more time per shot; (ii) have a higher low frequency band, square root of the mean of squared differences between successive R-R intervals (i.e. the time elapsing between two consecutive R waves in the electrocardiogram), and percentage of successive normal-to-normal intervals greater than 50 ms; and (iii) demonstrate an increase in parasympathetic nervous system activity compared with pre-competition values. We propose that these characteristics of experienced archers are appropriate for optimal performance during competition.